(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In today’s digital era, social media platforms have transformed how cosmetic brands connect with consumers. Advertising is no longer a one-way message; it’s interactive, emotional, and driven by trusted personalities. For beauty consumers, especially younger audiences, what they see on Instagram, YouTube, or TikTok plays a crucial role in shaping their buying decisions. Increasingly, consumers are also valuing brands that promote eco-friendly practices and sustainable beauty solutions, making sustainability an essential component of advertising strategies. This paper proposes a conceptual framework using the Theory of Planned Behaviour (TPB) to explore how specific features of social media advertising such as informativeness, interactivity, emotional appeal, credibility, and sustainability cues impact consumer attitudes and perceived social influence, ultimately affecting purchase intention. By integrating these advertising attributes into a behavioural model, the study offers a fresh perspective on how digital content design can shape beauty-related buying decisions. The proposed framework aims to guide future empirical research and help marketers design content that not only grabs attention but genuinely influences consumer behaviour.